Penyakit Karat Bawang Daun yang Disebabkan oleh Puccinia allii Rud. - Widodo, Widodo; Pamungkas, Ginting Tri; Susetyo, Hendry; Setiawan, Antoni; Wowor, Johanis (Jurnal Fitopatologi Indonesia, 2017)
New disease of bunching onion (Allium fistulosum) with typical symptoms as rust disease was found in the sub-district of West Tompaso and Modoinding, District of South Minahasa, North Sulawesi in June 2016. Infected plants in the field showed yellowish brown pustules on leaf surface, followed by leaf yellowing and drying out started from the tip. Disease incidence in surveyed area reached 100% with disease severity between 30%–50%. Based on microscopic observation of the fungal morphological characteristic, i.e. uredium dan urediniospora, the causal agent was identified as Puccinia allii Rud.